Housing affordability: Beyond the income and price terms, using China as a case study. (June 2015) - Cai, Wenjie; Lu, Xinhai
Abstract: A comprehensive understanding of housing affordability is essential for developing policies to deal with deteriorating housing affordability observed in major market economies in recent years. This paper proposes a broader housing appropriateness concept with four dimensions – affordability, accessibility, amenity and adequacy – which goes beyond the price and income terms widely used in research to measure housing affordability. It puts forward that trade-offs may occur in these dimensions, resulting in dynamic shifts of housing problems from one dimension to another. Then a case study in Wuhan, China is applied to exemplify how trade-offs happen in specific national contexts. The results show trade-offs between affordability and adequacy among income-constrained consumers and between adequacy and affordability as well as accessibility for an affordable housing policy. These findings suggest that a more dynamic and holistic view is needed when evaluating housing affordability problems and developing policy strategies accordingly. Highlights: Measurement of housing affordability issues goes beyond income and price terms. A broader concept covers affordability, accessibility, amenity, and adequacy. A case study, based on Wuhan, China, is applied to exemplify potential trade-offs between these dimensions. Trade-offs between affordability and adequacy among income-constrained consumers. Trading affordability and accessibility for adequacy for a housing policy.